On the upper and lower functions for sums of independent random variables with a limiting stable distribution - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Калинаускайте, О верхних и нижних функциях для сумм независимых случайных величин с предельными устойчивыми распределениями N. Kalinauskaitė, Nepriklausomų atsitiktinių dydžių sumų su ribiniais stabiliais pasiskirstymais viršutinių ir apatinių funkcijų klausimu